Defect Formation Mechanisms and Point Defect Concentrations in the Anion Sublattice of Uranium Dioxide: Molecular Dynamics Study (Communications in Computational Physics, 2018)
Anion defect concentrations in the uranium dioxide were calculated in awide temperature range by the molecular dynamics (MD) method, and a good agreementwith the neutron scattering experimental data is shown. Groups of isolatedinterstitial anions with the absence of anion vacancies in N nearest neighborhoods(N=1−4) were extracted, formation energies of each group in the different phasestates were derived.The formation energy of anion defects 4eV, derived by the MD method at low temperatures,in general coincides with the experimental estimations (3–4)eV and the latticestatic results 4.1eV, using the same interaction potential. At high temperatures inthe superionic state anion Frenkel defects (with N=3,4) have negative formation energyof about (-14)eV, concentrations of these defects are very small compared withthe total defect concentration, including non-stoichiometric crystals. The validity ofthe point defects model in the superionic state and transition regions is also discussed.The model of anion diffusion via the formation of short-living pairs "vacancy-interstitial anion" is proposed and confirmed by MD calculations. It is shown thatin the superionic state the exchange mechanism dominates, and at low temperatures itcoexists with the diffusion via the formation of long-living anion Frenkel pairs.